Diplomasi Human Security melalui Implementasi Kebijakan Nasional dalam Pengelolaan Pengungsi di Pekanbaru - Salsabila, Aurin; Encik Rania Olivia (Jurnal Transformasi Global, 2026)
The refugee issue in Pekanbaru reflects the challenges of implementing the human security principle at the local level. Although Presidential Regulation No. 125 of 2016 regulates the national framework for refugee management, its implementation reveals coordination gaps among local governments, international organizations, and the community. Previous studies have largely focused on the roles of IOM and UNHCR, leaving limited attention to the local government’s practical role, particularly that of Kesbangpol. This study aims to analyze how human security diplomacy is operationalized through the implementation of national policies in refugee management in Pekanbaru. The research employs a Systematic Literature Review and in-depth interviews with Kesbangpol officials. The findings point out that Pekanbaru government plays a crucial role in facilitating administrative processes, coordinating with relevant institutions, and conducting social outreach to communities. However, challenges persist, including limited resources, non-transparent coordination with IOM, and social resistance from local residents. Pekanbaru government seeks to balance refugee protection and social stability through a humanitarian and collaborative communication approach. The study concludes that effective human security diplomacy at the local level requires institutional synergy and adaptive policies to ensure that human protection principles align with local interests.